2019
DOI: 10.2478/vzoo-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Biological Characteristics of Amidostomum Anseris (Nematoda, Amidostomatidae) from Anser anser domesticus

Abstract: Morphological characteristics were studied in adult and embryonic Amidostomum anseris (Zeder, 1800) obtained from domestic goose Anser anser domesticus Linnaeus, 1758. The studied characters included species-specific morphometric indices of male and female specimens and differential characters of sex-related dimorphism in that species. Stages and periods of embryonic development, and viability of the nematodes were studied at laboratory conditions. Size dimorphism in A. anseris was considerable, females were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
1
0
5
Order By: Relevance
“…Other taxonomic features proposed to be used in the identification of Trichostrongyloidea are the specifics of the morphological structure and location of the lateral cuticular crests (wings, outgrowths) on the body of the parasite. Based on these features, keys have been proposed that increase the efficiency of differentiation of this group of nematodes (Lee, 1965;Hoberg & Lichtenfels, 1994;Lichtenfels et al, 1996;Yevstafieva et al, 2019). Studies have shown that the lateral cuticular crests on the entire body in T. tenuis females have different sizes in terms of height, width, and location relative to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Other taxonomic features proposed to be used in the identification of Trichostrongyloidea are the specifics of the morphological structure and location of the lateral cuticular crests (wings, outgrowths) on the body of the parasite. Based on these features, keys have been proposed that increase the efficiency of differentiation of this group of nematodes (Lee, 1965;Hoberg & Lichtenfels, 1994;Lichtenfels et al, 1996;Yevstafieva et al, 2019). Studies have shown that the lateral cuticular crests on the entire body in T. tenuis females have different sizes in terms of height, width, and location relative to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Собаки з фекаліями виділяють у навколишнє середовища яйця паразита, де і відбувається їхній ембріональний розвиток та дозрівання до інвазійної стадії. Останні здатні вже заражати дефінітивного хазяїна (Kirkova & Dinev, 2005;Yevstafieva et al, 2019). Автори зазначають, що яйця трихурисів є досить стійкими до умов зовнішнього середовища та здатні достатньо тривалий час зберігати свою інвазійність (Thapar & Singh, 1954;Mamedova & Fataliev, 2009).…”
Section: вступunclassified
“…У курей діагностовано гетеракоз, аскаридіоз, капіляріоз та трихостронгільоз, у гусей -гетеракоз, амідостомоз, капіля-ріоз та трихостронгільоз. Про значне розповсюдження цих збудників на території господарств різної форми власності Полтавської області свідчать результати наукових досліджень авторів (Yevstafieva et al, 2018;Yevstafieva et al, 2019). Так, у птахогосподарствах із підлоговою системою утримання курей середня екстенсивність капіляріозної інвазії становила 30,78 % за інтенсивності інвазії -23,57 ± 0,42 яєць у 1 г посліду (Yevstafieva  Natjaglaja, 2016).…”
Section: результати та їх обговоренняunclassified